7-6(-4k-5)=

Simple and best practice solution for 7-6(-4k-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-6(-4k-5)= equation:


Simplifying
7 + -6(-4k + -5) = 0

Reorder the terms:
7 + -6(-5 + -4k) = 0
7 + (-5 * -6 + -4k * -6) = 0
7 + (30 + 24k) = 0

Combine like terms: 7 + 30 = 37
37 + 24k = 0

Solving
37 + 24k = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-37' to each side of the equation.
37 + -37 + 24k = 0 + -37

Combine like terms: 37 + -37 = 0
0 + 24k = 0 + -37
24k = 0 + -37

Combine like terms: 0 + -37 = -37
24k = -37

Divide each side by '24'.
k = -1.541666667

Simplifying
k = -1.541666667

See similar equations:

| x(2x+2)=-30 | | 3x=7y+11 | | 7y+1=6y-3 | | X^5+x^4-2x^3-2x^2+x+1=0 | | M(x-n)=nx+s | | x-2/16=x/8 | | 7+y=4(3-y) | | 4(2x-1)=6x+10 | | 7y+2-5y=14+3y-4 | | 120/25x=45x | | 2x+(2x+7)=x(x+23) | | 16/x-6-192/x2-36=1 | | x(x+6)=247 | | 3x^2+4xy+6y=14 | | 5-3=v/12 | | 3*9.7=4*40 | | 2a+(2-a)=3 | | T/4=4 | | 12ac^3+12a^3b=0 | | N/10=2*5 | | 2x+y=y | | 3*10.3=4+10 | | x+(x-9)=12 | | 2x+(2-x)=3 | | 4z-5=z+4 | | Z+6=-15 | | -5-3(-5)y=1 | | 4+9=x(x+9) | | 6-7y=8-8y | | Y=0.09x+2.75 | | x-50*.85=143 | | 5(-6)-2y=10 |

Equations solver categories